2014
DOI: 10.3892/ijo.2014.2758
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA HOTAIR is associated with human cervical cancer progression

Abstract: The functions of many long non-coding RNAs (lncRNAs) in human cancers remain to be clarified. The lncRNA Hox transcript antisense intergenic RNA (HOTAIR) has been reported to reprogram chromatin organization and promote breast and colorectal cancer metastasis, the involvement of lncRNAs in cervical cancer is just beginning to be studied. In the present study, we examined the expression and the functional role of HOTAIR in cervical cancer. HOTAIR expression was determined in cervical cancer tissues (n=111) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
168
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(177 citation statements)
references
References 41 publications
9
168
0
Order By: Relevance
“…In cervical cancer, many LncRNAs have been found to suppress metastasis, as well as help in the prediction of metastasis through their expression levels (15). HOX transcript antisense intergenic RNA (HOTAIR) has been identified as an upregulated LncRNA in cervical cancer (16), and a recent study has revealed that HOTAIR enhanced aggressive biological behavior and induced radio-resistance via inhibiting p21 in cervical cancer, which proposed that targeting HOTAIR might be a potent therapeutic strategy in cervical cancer, especially for those patients who were administered radiotherapy (17). However, little is known about the overall biological role of HOTAIR in cervical cancer, or the underlying molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In cervical cancer, many LncRNAs have been found to suppress metastasis, as well as help in the prediction of metastasis through their expression levels (15). HOX transcript antisense intergenic RNA (HOTAIR) has been identified as an upregulated LncRNA in cervical cancer (16), and a recent study has revealed that HOTAIR enhanced aggressive biological behavior and induced radio-resistance via inhibiting p21 in cervical cancer, which proposed that targeting HOTAIR might be a potent therapeutic strategy in cervical cancer, especially for those patients who were administered radiotherapy (17). However, little is known about the overall biological role of HOTAIR in cervical cancer, or the underlying molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…[85][86][87][88][89] HOTAIR expression supports metastasis in breast cancer and has been linked to poor outcome in several malignancies. 85 Padua Alves et al 86 examined breast and colon cancer cell lines in studies of HOTAIR regulation and found that this lncRNA was increased after TGFβ1 treatment in both breast and colon cancers.…”
Section: Hox Transcript Antisense Intergenic Rna (Hotair)mentioning
confidence: 99%
“…86 HOTAIR has also been implicated in the regulation of CSCs in cervical cancer and endometrial cancer. [87][88][89] LINC-ROR Linc-ROR was first discovered in induced pluripotent stem cells (iPSCs) where it was regulated by the key pluripotency factors Oct4, Sox2 and Nanog. 90 Linc-ROR has a principal role in maintenance of iPSCs and embryonic stem cells by preventing the activation of cellular stress pathways including the p53 response.…”
Section: Hox Transcript Antisense Intergenic Rna (Hotair)mentioning
confidence: 99%
“…Numerous studies revealed the potential role of lncRNAs molecules in cervical cancer progression, invasion and metastasis. For example, reports have shown that lncRNA HOTAIR is significantly overexpressed in cervical cancer and furthermore its expression is correlated with tumour progression and metastasis and can predict a poor prognosis in patients with cervical cancer 13, 27, 28. Another intensely studied lncRNAs in cervical oncogenesis is MALAT1 who was found to be highly expressed in cancer advances stages, shown to promote proliferation, growth and invasion and overall can predict a poor prognosis 29, 30.…”
Section: Discussionmentioning
confidence: 99%